Implementation of Passive Deterioration Index Alerts in an Intermediate Care Unit: A Failed Early Warning System Strategy - Byrd, Thomas F., IV; Mattson, Molly; Polt, Mary; Pint, Katie; Dimitrov, Kiril; Willis, Angelica; Lister, Julia; Beacom, Evan; Tignanelli, Chris (Applied Clinical Informatics, 2025)
Traditional early warning systems (EWS) have shown uncertain efficacy in real-world settings. More recently, machine learning models like the Epic Deterioration Index (DTI) have been developed, promising greater accuracy. Recognizing the potential of DTI, but also the pervasive issue of alert fatigue with interruptive (i.e., pop-up) EWS alerts, our institution implemented a DTI-enabled EWS with passive alerts (colored icons visible in prespecified locations within the electronic health record). We hypothesized that our intervention would reduce the time to treatment for deteriorating patients.We piloted a DTI-enabled EWS in a 30-bed intermediate care unit at a large academic medical center. DTI scores, alert icons, and vital signs appeared on a custom Patient List interface. In the event of an alert, charge nurses were expected to conduct a bedside assessment and escalate care as necessary. We compared the 111-day pre- and postimplementation periods, with alert-to-action time as the primary outcome. Secondary outcomes included mortality, length of stay, ICU transfer, documentation rate, and provider acceptance.Among 301 patients with an elevated-risk score (156 pre- and 145 postimplementation), we found no significant differences in alert-to-action time (469 vs. 359 minutes before alert; p = 0.96), with provider actions typically occurring several hours before the alert in both periods. There were no significant differences in mortality (10.3% vs. 13.1%; p = 0.56), length of stay (15.7 vs. 12.8 days; p = 0.23), or ICU transfer (8.3% vs. 6.2%; p = 0.63). Charge nurses documented acknowledgment of the alert in 18.6% of cases, and acceptance was poor. Most nurses expressed a preference for interruptive alerts and more prominent DTI display locations.In this single-unit pilot, passive DTI-enabled EWS alerts did not improve time to intervention or clinical outcomes. High-risk DTI scores often occurred after clinical deterioration had already been recognized.
Keywords: severity of illness index; machine learning; decision support systems; length of stay; mortality